New ventures' collaborative linkages and innovation performance: Exploring the role of distance. (3rd April 2017) - Bolívar–Ramos, María Teresa
Abstract: In an era of globalization, new ventures have become especially active in collaborations with external partners worldwide to overcome the liability of newness and to obtain the resources required to innovate. In this context, this study conceptually analyzes how the geographical and institutional distances between a new venture and its international partners may influence the venture's ability to benefit from broad external linkages for innovation purposes. It proposes that the interplay of these factors affects not only knowledge transfer, but also business relations. The study advances theory on international collaborative linkages and innovation, by providing a novel framework that explains how contextual factors associated with distance affect the relation between new ventures' collaborations and their ability to develop innovations.